Development of high-performance motors for electromobilities - Guo, Feifan (Nanyang Technological University, 2022)
This report designs an interior permanent magnet synchronous motor for e-bike by utilizing Ansys Maxwell. The motor with mechanical gear is suitable for flat area and uphill riding. The IPMSM produces permanent magnet torque and reluctance torque, so it has a higher torque density. Different from induction motor, without secondary winding copper loss, IPMSM can reach a higher efficiency. The efficiency can reach 94.3% in this project. The design of the motor refers to Prius 2004. Optimization of the slot area that uses parametric modeling is made to improve the torque density. Then, the skew rotor is used to reduce torque ripple. The motor efficiency map which is generated by finite element analysis simulation is also used to find the rated operation point that meets the design demand and reach the optimal efficiency. Compare with the traditional method by making a prototype and testing it on different rotational speeds, simulation efficiency map can save a lot of time and its error is acceptable.